2008
DOI: 10.1111/j.1872-034x.2008.00423.x
|View full text |Cite
|
Sign up to set email alerts
|

Impaired liver regeneration in acute liver failure: the significance of cross‐communication of growth associated factors in liver regeneration

Abstract: Liver regeneration is considered to be retarded or suppressed in patients with acute liver failure. However, the mechanisms for this suppression remain to be elucidated. In order to evaluate deficiencies in liver regeneration in patients with acute liver failure, we focused on the cross-communication of growth-associated factors in experimental models. In primary cultured rat hepatocytes, the levels of cellular p53 and transforming growth factor-alpha (TGF-alpha), as well as DNA synthesis increased by the addi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 38 publications
0
2
0
1
Order By: Relevance
“…The effects are generated through the HGF/MET axis [17,18]. Several studies have confirmed that HGF can promote cell proliferation and migration and inhibit apoptosis and tissue fibrosis [19][20][21].…”
Section: Discussionmentioning
confidence: 99%
“…The effects are generated through the HGF/MET axis [17,18]. Several studies have confirmed that HGF can promote cell proliferation and migration and inhibit apoptosis and tissue fibrosis [19][20][21].…”
Section: Discussionmentioning
confidence: 99%
“…[47][48][49][50] The ability of primary hepatocytes to form tissue-like structures on micromolded PEG-fibrinogen gels in the absence of any of these growth factors provided exogenously implicates autocrine signaling. To examine the presence of autocrine growth factors, primary hepatocytes were cultured in serum-free medium devoid of exogenous growth factors and then fixed and stained with antibodies against EGF, HGF, and TGF-a at days 3, 7, and 10.…”
Section: Primary Hepatocytes Retain Cell-derived Fn and Growth Factormentioning
confidence: 99%
“…После обширных резекций выделенный клетками в ответ на повреждение фактор роста гепатоцитов способствует регенерации поврежденной печени, активизирует белково-синтетическую функцию печени [19,21,24].…”
unclassified